2016
DOI: 10.3889/oamjms.2016.008
|View full text |Cite
|
Sign up to set email alerts
|

Expression of OCT-4 and SOX-2 in Bone Marrow-Derived Human Mesenchymal Stem Cells during Osteogenic Differentiation

Abstract: AIM: Determine the levels of expression of pluripotency genes OCT-4 and SOX-2 before and after osteogenic differentiation of human mesenchymal stem cells (hMSCs).METHODS: Human MSCs were derived from the bone marrow and differentiated into osteoblasts. The analyses were performed on days 0 and 14 of the cell culture. In vitro differentiation was evaluated due to bone markers – alkaline phosphatase (AP) activity and the messenger RNA (mRNA) expression of AP and bone sialoprotein (BSP). The OCT-4 and SOX-2 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…Further analysis of protein expression in subsequent passages could provide more information about the correlation between the gene and protein expression of the markers. Moreover, it is important to mention, that MSCs expanded in culture with bFGF were found to have downregulated SOX2 mRNA suggesting bFGF as a potential factor affecting the expression of transcriptional factors [116]. Therefore, defining a cell state and phenotype solely on transcript expression can be unreliable and protein analysis has to be included.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of protein expression in subsequent passages could provide more information about the correlation between the gene and protein expression of the markers. Moreover, it is important to mention, that MSCs expanded in culture with bFGF were found to have downregulated SOX2 mRNA suggesting bFGF as a potential factor affecting the expression of transcriptional factors [116]. Therefore, defining a cell state and phenotype solely on transcript expression can be unreliable and protein analysis has to be included.…”
Section: Discussionmentioning
confidence: 99%
“…Ben-Shushan et al showed that the extinction of POU5F1 gene activity in stem cell-fibroblast hybrid cells was accompanied by fast methylation of regulatory sequences, such as proximal and distal enhancers in the POU5F1 promoter/enhancer region [45,46]. The expression of Oct4 and/or NANOG as markers of pluripotency was also demonstrated in BM-MSCs and in human multipotent adult SCs generated in vitro from adult human liver, heart, and BM [47,48] Previously, it was shown that DMSO can cause arrest of cells in the G1 phase, a process that is regulated by p21 and cyclin D1 cell cycle regulators [26][27][28]. In this study, DMSO and the process of freezing did not significantly change the expression of p21 and cyclin D1 genes in hAFSCs, indicating the applicability of this cryopreservation protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of OCT-4 expression almost exclusively around the hemmule border assumes significance because the expression of OCT4 in bone marrow mesenchyme cells indicated osteogenic differentiation [39]. Similarly, the distribution of SOX2 scattered cells was predominantly found around the hemmule edges ( Figure S12).…”
Section: Individual Cells Stained By Stem Cell Antibodies In Hemmulementioning
confidence: 93%